2022
DOI: 10.1155/2022/4172531
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Computational Analysis of Honokiol Targets for Cell Cycle Inhibition and Immunotherapy in Metastatic Breast Cancer Stem Cells

Abstract: Breast cancer stem cells (BCSCs) play a critical role in chemoresistance, metastasis, and poor prognosis of breast cancer. BCSCs are mostly dormant, and therefore, activating them and modulating the cell cycle are important for successful therapy against BCSCs. The tumor microenvironment (TME) promotes BCSC survival and cancer progression, and targeting the TME can aid in successful immunotherapy. Honokiol (HNK), a bioactive polyphenol isolated from the bark and seed pods of Magnolia spp., is known to exert an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…In a bioinformatic study, the potential targets and molecular mechanisms of honokiol in breast cancer stem cells were revealed ( 64 ). Honokiol inhibits the cell cycle via the PI3K/Akt/mTOR pathway by upregulating PTEN and P21 and suppressing p-Akt, cyclin D/CDK4, c-Myc, Rac1, and aurora kinase B. Honokiol can effectively block vascular endothelial growth factor receptor (VEGFR) 2 and suppress angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a bioinformatic study, the potential targets and molecular mechanisms of honokiol in breast cancer stem cells were revealed ( 64 ). Honokiol inhibits the cell cycle via the PI3K/Akt/mTOR pathway by upregulating PTEN and P21 and suppressing p-Akt, cyclin D/CDK4, c-Myc, Rac1, and aurora kinase B. Honokiol can effectively block vascular endothelial growth factor receptor (VEGFR) 2 and suppress angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol inhibits the cell cycle via the PI3K/Akt/mTOR pathway by upregulating PTEN and P21 and suppressing p-Akt, cyclin D/CDK4, c-Myc, Rac1, and aurora kinase B. Honokiol can effectively block vascular endothelial growth factor receptor (VEGFR) 2 and suppress angiogenesis. It was also found that honokiol reduces hypoxia-inducible factor (HIF)-induced VEGFR/VEGF activation and inhibits MMP activity and cell migration ( 64 ). Also, honokiol can induce apoptosis by upregulating BAD (the BCL2-associated agonist of cell death), caspase-9, caspase-3, and caspase-8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The docking results were analyzed based on the best pose and score. The 2D and 3D interactions were visualized in accordance with previous studies [42,43].…”
Section: Molecular Dockingmentioning
confidence: 99%